Packed U-Cell topology: Structure, control, and challenges - Trabelsi, Mohamed Ali; Makhamreh, Hamza; Kukrer, Osman; Vahedic, Hani (Elsevier, 2021)
The Packed U-Cell (PUC) inverter has been recently considered as an interesting single-DC-source multilevel inverter (SDCS-MLI) topology due to its multiple features compared to the other MLI topologies. The main benefits of this topology are the flexibility in expanding to higher output levels while using an SDCS, enhancement of the filter bandwidth taking advantage of the switching states redundancy, high reliability, and cost reduction due to the utilization of a reduced number of active components, and high ride-through capability assured by the topology storage capacitors. © 2021 Elsevier Inc. All rights reserved.
Keywords: Grid connection; Lyapunov; Model predictive control; Multicarrier pulse width modulation; Packed U-cell inverter; PUC5; PUC7; Rectifier; Reduced sensors; Sliding mode control